PENGARUH DUE PROFESSIONAL CARE, BESARAN FEE AUDIT, TEKANAN ANGGARAN WAKTU TERHADAP KUALITAS AUDIT - Komang Agung Semarabawa; Ni Wayan Alit Erlina Wati (UNHI Press, 2022)
Audit quality reflects the performance and duties of the public accounting profession in creating reports for investors, the general public, the government, and other parties, with a focus on the audited reports' reliability and adherence to high ethical standards. This research examines audit quality in terms of adequate professional care, audit fees, and time limitations. The sample size is selected using non-probability sampling, and the study style is associative research using a quantitative approach (saturated sampling). A total of 66 auditors were selected using questionnaires and data analysis with multiple linear regression tests. The research was carried out in the Bali Province Public Accountant Office. The purpose of using agency theory is to learn more about how management interacts with corporate agents. The data show that adequate professional care and the amount of the audit charge have a positive and significant influence on audit quality, but time budget constraints have a negative and significant impact